Optimizing Treatment in Luminal Breast Cancer - Nichols, Emma Hitt (MD Conference Express, 2012)
This article discussed the curability of luminal A and luminal B breast cancer subtypes, pharmacogenetics/pharmacogenomics to optimize endocrine therapy, new targeted agents in luminal breast cancer, as well as a review of whole genome sequencing for luminal-type breast cancer [Ellis MJ et al. Nature 2012].